A Coding of Real Null Four-Momenta into World-Sheet Coordinates. (22nd October 2008) - Fairlie, David B.
Abstract : The results of minimizing the action for string-like systems on a simply connected world sheet are shown to encode the Cartesian components of real null momentum four-vectors into coordinates on the world sheet. This identification arises consistently from different approaches to the problem.